Six-minute walking test in children. (8th January 2013) - Boucault, Roberta; Fernandes, Marcelo; Carvalho, Vitor Oliveira
Abstract : Implications for Rehabilitation: Six-minute walking test. The six-minute walking test is safe and widely performed in the world because of its easy implementation and low cost. Many countries have established normal values to the six-minute walking test in healthy children. However, the applicability of this test also gains popularity among children with other disease conditions.